VITRIFICATION OF BIOLOGICAL MATERIALS BY SLUSH NITROGEN - Silva, Alisson; Copetti, Jacqueline; Schroer, Ionatan; Souza, William; Chanan, Matheus; Cuieca, Massoxi; Macagnan, Mario; Oliveira, Jeferson; Cardoso, Elaine [UNESP]; Ogliari, Karolyn; Ascis, D.; Chrz, V; et al. (Int Inst Refrigeration, 2023)
This work presents the results of an experimental and theoretical study of cryopreservation applied to biological material (BM) using liquid (LN2) and slush (SN2) nitrogen. Cryotubes containing cryoprotectant solutions of DMSO, glycerol and sucrose diluted in phosphate buffered saline (PBS) solution and the freezing medium for semen TYB were immersed in both cryogenic fluids. Vitrification was also verified depending on the cryoprotective agent (CPA) concentration and sample volume. In case of immersion into SN2 greater freezing rates and vitrification were achieved for smaller volume and CPA concentration in comparison with immersion into LN2. Visually, the low occurrence of vaporization on the surface of the cryotube immersed into SN2 was observed. The numerical simulations with CFD (Computational Fluid Dynamics) allowed to analyze a vitrification system using the cryogenic fluids, obtaining their cooling and solidification curves, as well as the vapor contours for different instants of time.
Keywords: Cryopreservation; Vitrification; Slush nitrogen; Numerical simulation